PENGARUH LATIHAN BOOMERANG RUN DAN LATIHAN LADDER DRILLS TERHADAP KETERAMPILAN DRIBBLING SEPAKBOLA PEMAIN - Azizul Wildan Ramadhani; Kriswantoro Kriswantoro (Universitas Negeri Semarang, 2023)
The problem with this research is that dribbling techniques have an important effect on soccer games. Is there any effect of boomerang run and ladder drills training on dribbling skills? The purpose of this study was to determine 1. The effect of boomerang run training on dribbling skills, 2. The effect of ladder drills training on dribbling skills, and 3. Which of the two exercises is more effective on dribbling skills. The research method uses an experiment with a matched subject research design. The sample of this research is 22 people. The sampling technique used purposive sampling. The research variables are boomerang run and ladder drills. The data collection method used a dribbling skill test instrument. The results of the 1. Boomerang run exercise analysis obtained tcount 4,187 > ttable 2,228. 2. Ladder drills exercise obtained tcount 5,093 > ttable 2,228, meaning that both exercises have an effect on dribbling skills. 3. From the results of the subsequent analysis, it was found that the ladder drills exercise was more than the boomerang run exercise but it was not significant. The results of the study concluded that both exercises have an influence on dribbling skills. Suggestions to the coach to use the 2 training methods are because they are proven to be able to improve dribbling skills